Estimating of the Impact of Human Capital on Economic Growth in Egypt: An Econometric Model - Abdel Baset, Wael (The Arab Journal of Administration, 2019)
In this paper, we discussed the theoretical framework of the relationship between human capital in the form of health and education and economic growth. Then, we examined the human capital and growth relationship in Egypt. Human capital is the most important element in any economic development strategy in any country. Investment in education and health through increasing the expenditure on these two are used by countries, which are targeting economic development and economic growth. Economists usually call expenditure on education and health, the human capital. In this paper, the author is estimating the impact of human capital on the economic growth in the Egyptian economy. Results show the significant impact of human capital on the economic growth in Egypt from 1980s until nowadays. In addition, the impact of education is approximately double of the health impact on economic growth, especially in the long run. Policy makers should take this in account when they are planning the future of the economic growth in Egypt. the study also designed to provide a set of recommendations that could contribute to activating the role of human capital on economic growth